A production and operations management study on Everlast Agro-Industrial Corporation - Cansapin, Mark Gabriel; Parenno, Kristina; Santos, Allan T. (Diliman, Quezon City College of Engineering, 2001)
Everlast Agro-Industrial Corporation, the subject of this study, is a feedmill owned by twenty-seven stockholders. The company produces feeds for hogs and chickens. The study aims to improve the company's production system by looking in detail on their strategic capacity planning, aggregate planning, supply chain management, inventory system, and forecasting method used. The group obtained pertinent data through observation of the production system of the company and interviews of key personnel. Historical data of production and sales are essential in this study. Through observation and review of historical data, the group identified three major problem areas related to production and operations management, namely (1) ineffective forecasting technique, (2) ineffective inventory policy, and (3) unbalanced line flow of production. The group recommends casual method of forecasting to effectively project demand requirements, which are vital input to strategic capacity planning and aggregate planning. To achieve this purpose better, a software algorithm was proposed that would efficiently project the product demands. Since the company has no systematic inventory control, the group recommends an Economic Order Quantity (EOQ) model with reorder point for each raw material. This should minimize the annual holding cost and ordering cost of the company. The company is expected to save Php 28,255.30 annually in this system. To address the bottleneck problem at the loading station, the group recommends the addition of one more worker in this area. With the planned adjustment, effective capacity is expected to increase by 7.83%
Feasibility study
Keywords: Everlast Agro-Industrial Corporation; Agricultural industry; Production engineering